A scanning electron microscope (SEM) study of the smear layer in root canals. - (:unkn) unknown (My University, 1990)
A Scanning Electron Microscope was used to study the so-called "smear layer" produced in biomechanically prepared root canals. Fine, freshly-extracted incisors were used and the canals instrumented with K-type files and irrigated with 5% NaOCI and 3% H2O2. The structure of the "smear layer" produced was investigated.